CW and passively Q-Switched operation of a Ho:YAG waveguide laser. (1st June 2017) - McDaniel, Sean A.; Berry, Patrick A.; Cook, Gary; Zelmon, David; Meissner, Stephanie; Meissner, Helmuth; Mu, Xaiodong
Abstract: We report the first demonstration of a Ho: YAG crystal fiber waveguide (CFW) laser operating at 2.09 µm. The CFW structure was produced by adhesive free bonding of holmium doped yttrium aluminum garnet core to an undoped yttrium aluminum garnet cladding. The laser produced CW output powers greater than 500 mW with slope efficiency of 17%. The same crystal when passively Q-switched with Cr: ZnSe, produced pulsed output with energies of 1 μJ at a repetition frequency of 442 kHz. Abstract : Highlights: First demonstration of a Ho: YAG rigid waveguide laser operating at 2.09 µm. Produced CW output powers greater than 500 mW with a slope efficiency of 17%. Produced pulsed output with energies of 1 μJ at a repetition frequency of 442 kHz. Propagation and Thermal mode of the waveguide architecture.